(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Since cell phones emit radiofrequency electromagnetic fields (EMFs), this study tested the hypothesis that cell phones placed near the heart may interfere with the electrical rhythm of the heart or affect the blood pressure. Following informed consent, eighteen randomly selected apparently healthy male volunteers aged 21.44 ± 0.53 years had their blood pressure, pulse rates and ECG measured before and after acute exposure to a cell phone. The ECG parameters obtained were: heart rate (HR), QRS complex duration (QRS), PR interval (PR) and Corrected QT interval (QTc). Results are presented as mean ± SEM. Statistical analyses were done using two-tailed paired t test for blood pressure and pulse rate data and one way ANOVA with a post hoc Tukey test for the ECG data. P<0.05 was considered statistically significant. The blood pressure and pulse rates before and after exposure to the cell phone showed no significant difference. The ECG parameters (HR: beats/min, QRS:ms, PR:ms and QTc respectively) did not differ before (66.33 ± 2.50, 91.78 ± 1.36, 151.67 ± 5.39 and 395.44 ± 4.96), during (66.33 ± 2.40, 91.11 ± 1.61, 153.67 ± 5.06 and 394.33 ± 4.05) and after calls (67.22 ± 2.77, 91.11 ± 1.67, 157.44 ± 4.46 and 396.56 ± 4.93) compared to baseline (67.17 ± 2.19, 94.33 ± 1.57, 150.56 ± 4.93 and 399.56 ± 3.88). These results suggest that acute exposure to EMFs from cell phones placed near the heart may not interfere with the electrical activity of the heart or blood pressure in healthy individuals.